Influence of Parent-grandparent Coparenting Conflict on Grandparents' Depression Mediated by Grandparents' Sense of Mastery and Moderated by Their Sense of Valued Elder - MENG Huilin, GUO Fei, CHEN Zhiyan (Zhongguo quanke yixue, 2023)
Background In China, 80% of the grandparents are taking part in caring for grandchildren. However, it has been found by available studies that involvement in taking care of grandchildren may increase the risk of depression among grandparents, which would seriously harm their quality of life, and the risk of depression is associated with parent-grandparent coparenting conflict, grandparents' sense of valued elder and sense of mastery, but the underlying mechanism still requires further investigation. Objective To investigate the influence of parent-grandparent coparenting conflict on grandparents' depression, and to explore the mediating and moderating mechanisms that grandparents' sense of mastery and sense of valued elder may play in it. Methods This study used two surveys. Grandparents (totally 626 cases) who participated in caring for grandchildren were selected by snowball sampling to attend an online survey or by convenience sampling to attend an offline survey from August to November 2021 using four questionnaires, namely the Coparenting Relationship Scale (CRS), the Pearlin Mastery scale (PMS), Grandparent Meaning Scale (GMS), and the 9-item Chinese version of the Center for Epidemiological Studies Depression Scale (CES-D-C). Pearson correlation was used to analyze the relationship of mother-grandparent coparenting conflict score, father-grandparent coparenting conflict score, PMS score, score of the valued elder dimension of the GMS and CES-D-C. PROCESS was used to examine the mediating effect of grandparents' sense of mastery and the moderating effect of their sense of valued elder between parent-grandparent coparenting conflict and grandparents' depression, and to draw a simple slope diagram. Results A total of 626 cases returned responsive questionnaires, with a response rate of 99.2%. The prevalence of depression tendency was 12.0% (75/626) in this study. The score of CES-D-C〔 (5.36±4.14) 〕 was found to be significantly positively correlated with mother-grandparent coparenting conflict score〔 (9.87±3.08), r=0.28, P<0.05〕, and father-grandparent coparenting conflict score〔 (7.34±3.25), r=0.35, P<0.05〕, but was negatively correlated with the PMS score 〔 (12.61±5.48), r=-0.25, P<0.05〕and the score of valued elder dimension〔 (84.13±8.58), r=-0.21, P<0.05〕. Grandparents' sense of mastery partially mediated the relationship of grandparents' depression with mother-grandparent coparenting conflict (with a size of indirect effect of 0.05, accounting for 17.2% of the total effects) and father-grandparent coparenting conflict (with a size of indirect effect of 0.04, accounting for 11.4% of the total effects). Grandparents' sense of valued elder moderated the relationship of grandparents' depression with mother-grandparent coparenting conflict (b=-0.06, P<0.05), and father-grandparent coparenting conflict (b=-0.07, P<0.05). The results of simple slope tests showed that among those with lower sense of valued elder, father-grandparent or mother-grandparent co-parenting conflict had a stronger influence on their depression than their counterparts with higher sense of valued elder. Conclusion Parent-grandparent (either mother-grandparent or father-grandparent) coparenting conflict is an important associated factor for grandparent's depression In this association, grandparent's sense of mastery plays a mediating role, while grandparent's sense of valued elder exerts a moderating effect. To reduce the risk of depression and promote the metal health among elders who take part in coparenting, efforts can be made to reduce coparenting conflicts and enhance the elders' sense of mastery and sense of valued elder.